PERLINDUNGAN HUKUM TERHADAP ANAK JALANAN SEBAGAI KORBAN EKSPLOITASI EKONOMI - Eka Aulia Novianti; Ida Budhiati; Diana Fitriani (JOURNAL OF LAW AND NATION, 2023)
The phenomenon of exploitation of street children, especially in Bekasi City, is a complex social problem. Living as street children is not a pleasant choice and their existence is often a problem for many parties, families, communities and countries, so it is very necessary to protect the exploitation of street children and the fulfillment of children's rights should receive serious attention. The purpose of the study was to determine the legal protection against the exploitation of street children in Bekasi City and to find out the obstacles faced regarding legal protection against the exploitation of street children in Bekasi City and their solutions. This research is sociological juridical research, namely juridical research is research that uses rules and legislation related to the problem under study, while sociological research is an approach that uses primary data with the support of secondary data. Primary data is data obtained from the community directly or obtained from law enforcement officials related to this study. Secondary data is data obtained by conducting literature research. The result of this study is that legal protection against the exploitation of street children in Bekasi City is included based on Mayor Regulation Number 1 of 2021 concerning Bekasi City Child Protection as a Legal Protection Arrangement for children victims of economic exploitation and with regulations to protect economically exploited children not balanced with the implementation of these regulations, So it is very possible that there are many problems that arise in these street children that cannot be resolved by law enforcement officials.